Bone Engineering of Maxillary Sinus Bone Deficiencies Using Enriched CD90+ Stem Cell Therapy: A Randomized Clinical Trial. (July 2015) - Kaigler, Darnell; Avila‐Ortiz, Gustavo; Travan, Suncica; Taut, Andrei D; Padial‐Molina, Miguel; Rudek, Ivan; Wang, Feng; Lanis, Alejandro; Giannobile, William V
ABSTRACT Bone engineering of localized craniofacial osseous defects or deficiencies by stem cell therapy offers strong prospects to improve treatment predictability for patient care. The aim of this phase 1/2 randomized, controlled clinical trial was to evaluate reconstruction of bone deficiencies of the maxillary sinus with transplantation of autologous cells enriched with CD90+ stem cells and CD14+ monocytes. Thirty human participants requiring bone augmentation of the maxillary sinus were enrolled. Patients presenting with 50% to 80% bone deficiencies of the maxillary sinus were randomized to receive either stem cells delivered onto a β‐tricalcium phosphate scaffold or scaffold alone. Four months after treatment, clinical, radiographic, and histologic analyses were performed to evaluate de novo engineered bone. At the time of alveolar bone core harvest, oral implants were installed in the engineered bone and later functionally restored with dental tooth prostheses. Radiographic analyses showed no difference in the total bone volume gained between treatment groups; however, density of the engineered bone was higher in patients receiving stem cells. Bone core biopsies showed that stem cell therapy provided the greatest benefit in the most severe deficiencies, yielding better bone quality than control patients, as evidenced by higher bone volume fraction (BVF; 0.5 versus 0.4; p = 0.04). Assessment of the relation between degree of CD90+ stem cell enrichment and BVF showed that the higher the CD90 composition of transplanted cells, the greater the BVF of regenerated bone (r = 0.56; p = 0.05). Oral implants were placed and restored with functionally loaded dental restorations in all patients and no treatment‐related adverse events were reported at the 1‐year follow‐up. These results provide evidence that cell‐based therapy using enriched CD90+ stem cell populations is safe for maxillary sinus floor reconstruction and offers potential to accelerate and enhance tissue engineered bone quality in other craniofacial bone defects and deficiencies (Clinicaltrials.gov NCT00980278). © 2015 American Society for Bone and Mineral Research. © 2015 American Society for Bone and Mineral Research